CaV2.1 ablation in cortical interneurons selectively impairs fast‐spiking basket cells and causes generalized seizures. Issue 2 (1st July 2013) - Rossignol, Elsa; Kruglikov, Illya; van den, Arn M. J. M.; Rudy, Bernardo; Fishell, Gord
<x xml:space="preserve">Abstract</x> Objective Both the neuronal populations and mechanisms responsible for generalized spike‐wave absence seizures are poorly understood. In mutant mice carrying loss‐of‐function (LOF) mutations in Cacna1a, which encodes the α1 pore‐forming subunit of CaV2.1 (P/Q‐type) voltage‐gated Ca2+ channels, generalized spike‐wave seizures have been suggested to result from excessive bursting of thalamocortical cells. However, other cellular populations including cortical inhibitory interneurons may contribute to this phenotype. We investigated how different cortical interneuron subtypes are affected by the loss of CaV2.1 channel function and how this contributes to the onset of generalized epilepsy. Methods We designed genetic strategies to induce a selective Cacna1a LOF mutation in different cortical γ‐aminobutyric acidergic (GABAergic) and/or glutamatergic neuronal populations in mice. We assessed the cellular and network consequences of these mutations by combining immunohistochemical assays, in vitro physiology, optogenetics, and in vivo video electroencephalographic recordings. Results We demonstrate that selective Cacna1a LOF from a subset of cortical interneurons, including parvalbumin (PV)+ and somatostatin (SST)+ interneurons, results in severe generalized epilepsy. Loss of CaV2.1 channel function compromises GABA release from PV+ but not SST+ interneurons. Moreover, thalamocortical projection neurons do not show enhanced bursting in these mutants, suggesting that this feature is not essential for the development of generalized spike‐wave seizures. Notably, the concurrent removal of CaV2.1 channels in cortical pyramidal cells and interneurons considerably lessens seizure severity by decreasing cortical excitability. Interpretation Our findings demonstrate that conditional ablation of CaV2.1 channel function from cortical PV+ interneurons alters GABA release from these cells, impairs their ability to constrain cortical pyramidal cell excitability, and is sufficient to cause generalized seizures. Ann Neurol 2013;74:209–222